Social networks and unraveling in labor markets - Itay P. Fainmesser (Brown University, Department of Economics, 2010)
This paper studies the phenomenon of early hiring in entry-level labor markets (e.g. the market for gastroenterology fellowships and the market for judicial clerks) in the presence of social networks. We offer a two-stage model in which workers in training institutions reveal information on their own ability over time. In the early stage, workers receive a noisy signal about their own ability. The early information is soft and non-verifiable, and workers can convey the information credibly only to firms that are connected to them (potentially via their mentors). At the second stage, hard verifiable (and accurate) information is revealed to the workers and can be credibly transmitted to all firms. We characterize the effects of changes to the network structure on the unraveling of the market towards early hiring. Moreover, we show that an efficient design of the matching procedure can prevent unraveling.
Keywords: A14; D85; C78; L14; 330; networks; market design; unraveling; entry-level labor markets; early hiring; Personalbeschaffung; Asymmetrische Information; Soziales Netzwerk; Berufsbildung; Berufseinstieg; Theorie